On monotonic determinacy and rewritability for recursive queries and views - Benedikt, M; Kikot, S; Ostropolski-Nalewaja, P; Romero, M (Association for Computing Machinery, 2023)
A query Q is monotonically determined over a set of views V if Q can be expressed as a monotonic function of the view image. In the case of relational algebra views and queries, monotonic determinacy coincides with rewritability as a union of conjunctive queries, and it is decidable in important special cases, such as for CQ views and queries [Nash et al. 2010; Benedikt et al. 2016]. We investigate the situation for views and queries in the recursive query language Datalog. We give both positive and negative results about the ability to decide monotonic determinacy, and also about the co-incidence of monotonic determinacy with Datalog rewritability.